2000
DOI: 10.1002/1099-0968(200008)8:4<293::aid-erv346>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for eating disorders from a patient satisfaction perspective: a Norwegian replication of a British study

Abstract: The purpose of this study was to replicate a British survey on patient satisfaction with treatment for eating disorders, factors associated with satisfaction and the consumer|s suggestions on how to improve the quality of health care services. A questionnaire was completed by 321 members of the Norwegian organizations for eating disorder patients. The British results were replicated as subjects were highly satisfied with outpatient individual and group psychotherapy, and to a less extent with family therapy. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
0
8

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 9 publications
6
60
0
8
Order By: Relevance
“…The second theme which emerged from participants' responses referred to types of interventions received, and, in accordance with previous findings, individual psychotherapy was highly valued (Bell, 2003;Escobar-Koch et al, 2010;Rosenvinge & Klusmeier, 2000). Patients in this study highlighted the benefits of cognitive-behavioral techniques, in line with a recent study in which patients with bulimia nervosa and eating disorder not otherwise specified responded well to cognitive-behavioral treatments (Fairburn et al, 2009).…”
Section: Resultssupporting
confidence: 84%
“…The second theme which emerged from participants' responses referred to types of interventions received, and, in accordance with previous findings, individual psychotherapy was highly valued (Bell, 2003;Escobar-Koch et al, 2010;Rosenvinge & Klusmeier, 2000). Patients in this study highlighted the benefits of cognitive-behavioral techniques, in line with a recent study in which patients with bulimia nervosa and eating disorder not otherwise specified responded well to cognitive-behavioral treatments (Fairburn et al, 2009).…”
Section: Resultssupporting
confidence: 84%
“…2,6,7 Most studies of client satisfaction have low participation rates. 3,8,9 Patients who have dropped out of treatment are seldom included, and participants are often selfselected from patient associations or self-help groups. These participants may differ significantly from patients with eating disorders (ED) treated by health services.…”
Section: Introductionmentioning
confidence: 99%
“…These participants may differ significantly from patients with eating disorders (ED) treated by health services. [9][10][11] Knowledge is lacking on whether client satisfaction is related to outcome in patients with ED.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The earlier studies, which were published between 1990 and 2005, showed that most of the patients who were interviewed preferred individual therapy, group therapy and selfhelp groups than other forms of treatment, such as inpatient programs [9,10]. Interestingly, the more "specialized" therapies, such as behavioral and family therapy, were not regarded positively by the patients [9,10]. The majority of the patients were more satisfied when they were treated in a specialized unit for ED's or by a therapist experienced specifically in ED therapy [10,11].…”
Section: The Patient's Perspective Of Recovery From Eating Disordersmentioning
confidence: 99%